Intensitas Cahaya dan Efisiensi Fotosintesis pada Tanaman Naungan dan Tanaman Terpapar Cahaya Langsung - Yustiningsih, Maria (BIO-EDU: Jurnal Pendidikan Biologi, 2019)
Plant growth and productivity influenced by light. Sunlight activates light-dependent reactions or LDR and Calvin cycle or LIR in plant. Different light intensity induce change of LDR and LIR. Adaptation through efficiency of photon absorption, regulation of photosystem II - photosystem I, and carbon fixation can make photosynthesis efficiently. This paper aims to review research on photosynthesis mechanism in sun and shade plants. Alteration of light absorption in plants produce morphological and physiological adaptations. Plant adaptation mechanism use sieve effect, light channeling, and acclimatization. Distribution of chlorophyll in both types of plants changed the photosynthesis photon flux density. Propagation and distribution of light needed through vacuoles to minimize the distance on electron transport chain. Physiological acclimatization accelerates by changing the composition of chlorophyll and PSII / PSI ratio. Shade plants have a high ratio PS II / PSI and high ratio chlorophyll a / b to increase the light-harvesting complex and make photosynthesis efficiently.